Microstructure and mechanical properties of a new nickel-based single crystal superalloy - Zhao Shang; Xianping Wei; Dazhuo Song; Juntao Zou; Shuhua Liang; Gang Liu; Liping Nie; Xiufang Gong (Journal of Materials Research and Technology, 2020)
To obtain higher comprehensive mechanical properties while avoid the adverse effects of Re element on the microstructure and economy of the alloy, a Re-free nickel-based single crystal superalloy is developed based on the Rene N5 single crystal superalloy. The microstructure evolution, compression properties, tensile properties, deformation mechanism and fracture behaviour of the self-designed alloy are investigated. The experimental results show that after the complete heat treatment, cuboidal γ′ precipitates with high degree of regular morphology are formed. The size of γ′ precipitates is about 0.49 μm, and the volume fraction is approximately 61%, which are better than those for a conventional second generation single crystal superalloy. The alloy reaches its maximum compressive and tensile strength at 760 °C and shows excellent microstructure thermal stability and improved mechanical properties. The alloy has an obvious strain hardening stage when the temperature is lower than 760 °C, while the softening stage is not obvious. When the temperature reaches 850 °C, the stress–strain curve of the sample mainly shows that the variable stress increases abruptly at the beginning and then decreases immediately. The tensile fracture of a single crystal at medium and low temperature is characterized by a slip fracture with a certain plastic deformation. A high temperature tensile fracture is characterized by typical plastic deformation, and its mechanism is a creep fracture with a uniform deformation.